Pilot study of a Web-based acceptance and commitment therapy intervention for university students to reduce academic procrastination. Issue 4 (19th May 2019) - Gagnon, Joel; Dionne, Frédérick; Raymond, Guillaume; Grégoire, Simon
Abstract: Objective: This pilot study pursued two aims. The first was to investigate the feasibility and acceptability of a Web-based acceptance and commitment therapy (ACT) intervention to reduce academic procrastination among university students. The second aim was to test the effectiveness of the intervention on procrastination and committed actions.Participants: The sample was comprised of Canadian university students ( n = 36) that participated in the intervention between September 2016 and April 2017.Methods: The study relied on a prepost research design.Results: The intervention appears feasible, acceptable, and valuable to students. A significant reduction in procrastination and a significant improvement in committed actions were found between pre and postintervention. The effect sizes for these results were medium.Conclusions: Results provide preliminary support for the feasibility and effectiveness of a Web-based ACT intervention for academic procrastination. Results also highlight some aspects that need to be improved for further development.